2000
DOI: 10.1038/sj.onc.1203875
|View full text |Cite
|
Sign up to set email alerts
|

Rb and p130 regulate RNA polymerase I transcription: Rb disrupts the interaction between UBF and SL-1

Abstract: We have previously demonstrated that the protein encoded by the retinoblastoma susceptibility gene (Rb) functions as a regulator of transcription by RNA polymerase I (rDNA transcription) by inhibiting UBFmediated transcription. In the present study, we have examined the mechanism by which Rb represses UBFdependent rDNA transcription and determined if other Rb-like proteins have similar eects. We demonstrate that authentic or recombinant UBF and Rb interact directly and this requires a functional A/B pocket. DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 56 publications
(133 reference statements)
3
84
0
Order By: Relevance
“…7), consistent with a role for the Rb family of proteins in the regulation of rDNA transcription (Ciarmatori et al, 2001;Hannan et al, 2000). We, however, did not find any cells in the entire exponentially growing population (Figs 6, 7), which exhibited the limited perinucleolar pRb staining pattern described by Kennedy et al (Kennedy et al, 2000).…”
Section: Journal Of Cell Science 115 (21)mentioning
confidence: 46%
“…7), consistent with a role for the Rb family of proteins in the regulation of rDNA transcription (Ciarmatori et al, 2001;Hannan et al, 2000). We, however, did not find any cells in the entire exponentially growing population (Figs 6, 7), which exhibited the limited perinucleolar pRb staining pattern described by Kennedy et al (Kennedy et al, 2000).…”
Section: Journal Of Cell Science 115 (21)mentioning
confidence: 46%
“…Our data indicate that disruption of the SL1/rDNA complex by CX-5461 results from the interference between SL1 and rDNA and not through dissociation of protein-protein interactions, as was shown for several known tumor suppressors (p53, Rb, PTEN; refs. [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that pRb can be found in the nucleolus of quiescent or differentiating cells, where it binds UBF1 and causes a decrease in transcription from the rDNA promoter (29)(30)(31). It has also been reported that pRb binds to the pRb binding motif (LxCxE) of UBF1 (29), but subsequent reports have indicated that pRb binds to a different sequence of UBF1 (30). We first determined whether IRS-1 and pRb competed directly for binding to UBF1, and then we tested whether the expression of IRS-1 inhibited the occupancy of the rDNA promoter by pRb.…”
Section: Cancer Researchmentioning
confidence: 99%